Programa de Aprendizaje para el desarrollo de Competencias Emprendedoras en estudiantes del 5° secundaria. Institución Educativa Privada “Innova Schools”. Tacna, 2018. - Cardenas Vilcapaza, Luz Belinda (2019)
The type of research used was Propositiva, because a program for the development of entrepreneurial skills was proposed. Hernández, Fernández and Baptista mention that this type of research deals with how things should be to achieve certain ends and function properly. For the case study, from the descriptive study the need was identified and a solution was proposed through the proposal of business training strategies. (Hernández, 2010) The research design that has been used is the non-experimental design, since it will not be subject to any test system. According to Hernández, Fernández and Baptista (2010), what is done in non-experimental research is to observe phenomena as they occur in their natural context, and then analyze them. The study population is students of the 5th Secondary School of the Individual Educational Institution Innova Schools, consisting of 70 students. Twenty students of the 5th grade of secondary school were taken as sample, to apply the entry test on "Entrepreneurial skills" The instruments used in the present investigation would be the following: • Test of evaluation of entrepreneurial skills. It constitutes the entrance and exit test applied to the students, from which the input was applied, for the analysis of the results of this research work.